2016
DOI: 10.3390/proteomes4030024
|View full text |Cite
|
Sign up to set email alerts
|

Selecting Sample Preparation Workflows for Mass Spectrometry-Based Proteomic and Phosphoproteomic Analysis of Patient Samples with Acute Myeloid Leukemia

Abstract: Global mass spectrometry (MS)-based proteomic and phosphoproteomic studies of acute myeloid leukemia (AML) biomarkers represent a powerful strategy to identify and confirm proteins and their phosphorylated modifications that could be applied in diagnosis and prognosis, as a support for individual treatment regimens and selection of patients for bone marrow transplant. MS-based studies require optimal and reproducible workflows that allow a satisfactory coverage of the proteome and its modifications. Preparatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 39 publications
(69 reference statements)
1
15
0
Order By: Relevance
“…Various sample preparation methods have been described for bottom-up proteomics experiments targeting (solid) tissues, and a wide range of modifications to these methods can also be found in literature. 7 , 12 , 13 The most straightforward methods involve direct (in-solution) digestion of proteins without distinct procedures to remove contaminants including detergents, chaotropes, lipids, and nucleic acids. 7 , 9 , 10 In our study, we show that such an in-solution digestion (ISD) approach is a good option for quantitative proteomics featuring limited losses and good precision for peptide and protein quantification on the basis of simple and highly automatable workflows.…”
Section: Discussionmentioning
confidence: 99%
“…Various sample preparation methods have been described for bottom-up proteomics experiments targeting (solid) tissues, and a wide range of modifications to these methods can also be found in literature. 7 , 12 , 13 The most straightforward methods involve direct (in-solution) digestion of proteins without distinct procedures to remove contaminants including detergents, chaotropes, lipids, and nucleic acids. 7 , 9 , 10 In our study, we show that such an in-solution digestion (ISD) approach is a good option for quantitative proteomics featuring limited losses and good precision for peptide and protein quantification on the basis of simple and highly automatable workflows.…”
Section: Discussionmentioning
confidence: 99%
“…The methods for analysis of proteomic and phosphoproteomic profiles in primary human AML cells have been described in detail previously [74,75,76]. Briefly, each patient sample was spiked with a heavy super-SILAC mix [77] and prepared according to the filter-aided sample preparation protocol [78] for proteome and phosphoproteome analysis using nano-liquid chromatography online coupled with a QExactive HF Orbitrap mass spectrometer (Thermo Scientific, Bremen, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…We previously showed that a super-SILAC (Stable Isotope Labeling with Amino Acids in Cell Culture) mix based on five AML cell lines provided a solid reference for quantitative proteomics studies of AML patient cells [30]. Together with optimized sample preparation and phosphopeptide enrichment protocols, our proteomics workflows proved to be useful for the study of prognosis biomarkers and treatment response in AML [31][32][33].…”
Section: Introductionmentioning
confidence: 99%